Afrikaanse historici as politieke kritici en koers-aanduiders - De Klerk, Pieter (Faculty of Humanities, University of the Free State, 2012)
Although professional historians usually concentrate on specific areas of research, they sometimes use their knowledge and understanding of history to give a perspective on contemporary events and provide guidelines regarding the formulation and implementation of government policies. Since the 1950s Afrikaner historians have participated in intellectual debates on the future of the Afrikaners as a minority group in South Africa. Three eminent Afrikaner historians, GD Scholtz, FA van Jaarsveld and Hermann Giliomee, produced a number of publications in which they commented on the apartheid policy of the National Party government. While Scholtz and Van Jaarsveld were very subdued in their criticism, Giliomee was more openly critical. On the other hand, Scholtz and Giliomee were more consistent in their criticism than Van Jaarsveld, who repeatedly changed his views. Scholtz and Giliomee, however, overestimated the power of the government to control the factors that determined South Africa’s political and economic development during this period.
Keywords: Afrikaner historians; Political criticism; Afrikaner nationalism; Apartheid; Territorial separation; G. D. Scholtz; F.A. van Jaarsveld; H. Giliomee